PERAN MITRA USAHATANI TERHADAP PENGEMBANGAN USAHATANI TAMBAK UDANG DI DESA WAETUOE KECAMATAN LANRISANG KABUPATEN PINRANG - Hastina, Hastina; Nuddin, Andi; Nurhaedah, Nurhaedah (Fakultas Pertanian, 2024)
The Role of Farming Partners in the Development of Shrimp Farming in Waetuoe Village, Lanrisang District, Pinrang Regency, under the guidance of Andi Nuddin and Nurhaeda. This research was conducted in Lanrisang District, Pinrang Regency, from June 2024 to August 2024. The research aims to identify the income of shrimp farmers before and after partnering, the challenges faced by the farmers, and the strategic programs that can be implemented for the development of shrimp farming using a descriptive quantitative method with Interpretive Structural Modeling (ISM). The descriptive method research required a sample size of 33, while the ISM method required a smaller sample size, hence, only 7 people were sampled. The study employed primary and secondary data collection techniques, including observation, interviews, questionnaires, and documentation. Data processing was done by calculating income using the formula revenue - capital, which showed a slight increase in income after partnering. The most common challenge faced by farmers was shrimp disease outbreaks. The research began with editing, coding responses, and processing using Interpretive Structural Modeling (ISM), which identified increasing farmer knowledge as a priority program or key element.